Analysis of Factors Related to Visual Inspection with Acetic Acid Examination on Child Bearing Women - Yunitasari, Esti; Riantika, Eva; Yusuf, Ah; Aulia, Aria (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Not only the health promotion about Visual Inspection with Acetic Acid (VIA) examination and servical cancer but also free for VIA examination have been held in Polindes Tanjunganom, but the scope of VIA examination is still in low grade. Health Belief Model (HBM) theory is used to evaluate and explain the differences of individual perception towards preventive behaviors. This study was aimed to analyze the factors correlating with VIA examination in women by HBM. Design used in this study was cross sectional. The population was all child bearing women in Puskesmas Tanjunganom region. Total sample was 50 respondents, taken according to simple random technique. The independent variabels were perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, and cues to action. The dependent variabel was VIA examination. Data were collected by using structured questionnaire and analyzed by using chi square test with level of significance of â¤ 0,05. Results showed that perceived susceptibility had correlation with VIA examination (p=0,026), perceived seriousness had correlation with VIA examination (p=0,004), perceived benefits had correlation with VIA examination (p=0,016), perceived barriers had correlation with VIA examination (p=0,016), and cues to action (p=0,000) had correlation with VIA examination. It can be concluded that HBM has correlation with VIA examination and cues to action has the strongest variabel related to VIA examination. Further studies should involve larger respondents and better measurement tools to obtain more accurate results.